<em>1</em><em>/</em><em>2</em><em> </em><em>[</em><em> </em><em>(</em><em>3</em><em>/</em><em>2</em><em>)</em><em>y</em><em> </em><em>+</em><em> </em><em>1</em><em>/</em><em>3</em><em>]</em><em> </em><em>=</em><em> </em><em>-</em><em>1</em><em>/</em><em>2</em><em> </em><em>[</em><em>y</em><em>-</em><em>5</em><em>/</em><em>2</em><em>]</em>
<em>(</em><em>3</em><em>/</em><em>2</em><em>)</em><em>y</em><em> </em><em>+</em><em> </em><em>1</em><em>/</em><em>3</em><em> </em><em>=</em><em> </em><em>-</em><em>(</em><em>1</em><em>/</em><em>2</em><em>)</em><em>y</em><em> </em><em>+</em><em> </em><em>3</em>
<em>(</em><em>3</em><em>/</em><em>2</em><em> </em><em>+</em><em> </em><em>1</em><em>/</em><em>2</em><em>)</em><em>y</em><em> </em><em>=</em><em> </em><em>3</em><em> </em><em>-</em><em> </em><em>1</em><em>/</em><em>3</em>
<em>2y</em><em> </em><em>=</em><em> </em><em>8</em><em>/</em><em>3</em>
<em>y</em><em> </em><em>=</em><em> </em><em>4</em><em>/</em><em>3</em>
<u><em>y</em><em> </em><em>=</em><em> </em><em>1.33</em></u>
<em>#</em><em>$</em><em>#</em><em>HOPE</em><em> </em><em>YOU</em><em> </em><em>UNDERSTAND</em><em> </em><em>#</em><em>$</em><em>#</em>
<em>#</em><em>$</em><em>¥</em><em>THANK</em><em> </em><em>YOU</em><em> </em><em> ¥</em><em>$</em><em>#</em>
<em>❤</em><em> </em><em>☺</em><em> </em><em>☺</em><em> </em><em>☺</em><em> </em><em /><em> </em><em>☺</em><em> </em><em>☺</em><em> </em><em>☺</em><em> </em><em>❤</em><em> </em>
Answer:
![\sin(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=%5Csin%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Step-by-step explanation:
Given
![f(x) = \sin x\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csin%20x%5C%5C)
![c = \frac{3\pi}{4}](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7B3%5Cpi%7D%7B4%7D)
Required
Find the Taylor series
The Taylor series of a function is defines as:
![f(x) = f(c) + f'(c)(x -c) + \frac{f"(c)}{2!}(x-c)^2 + \frac{f"'(c)}{3!}(x-c)^3 + ........ + \frac{f*n(c)}{n!}(x-c)^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20f%28c%29%20%2B%20f%27%28c%29%28x%20-c%29%20%2B%20%5Cfrac%7Bf%22%28c%29%7D%7B2%21%7D%28x-c%29%5E2%20%2B%20%5Cfrac%7Bf%22%27%28c%29%7D%7B3%21%7D%28x-c%29%5E3%20%2B%20........%20%2B%20%5Cfrac%7Bf%2An%28c%29%7D%7Bn%21%7D%28x-c%29%5En)
We have:
![c = \frac{3\pi}{4}](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7B3%5Cpi%7D%7B4%7D)
![f(x) = \sin x\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csin%20x%5C%5C)
![f(c) = \sin(c)](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28c%29)
![f(c) = \sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f(c) = \sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f'(c) = \cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f'(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f'(c) = \cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f"(c) = -\sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f"(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f"(c) = -\sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f"'(c) = -\cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20-%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f"'(c) = - * -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20-%20%2A%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"'(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
So, we have:
![f(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f'(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"'(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f(x) = f(c) + f'(c)(x -c) + \frac{f"(c)}{2!}(x-c)^2 + \frac{f"'(c)}{3!}(x-c)^3 + ........ + \frac{f*n(c)}{n!}(x-c)^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20f%28c%29%20%2B%20f%27%28c%29%28x%20-c%29%20%2B%20%5Cfrac%7Bf%22%28c%29%7D%7B2%21%7D%28x-c%29%5E2%20%2B%20%5Cfrac%7Bf%22%27%28c%29%7D%7B3%21%7D%28x-c%29%5E3%20%2B%20........%20%2B%20%5Cfrac%7Bf%2An%28c%29%7D%7Bn%21%7D%28x-c%29%5En)
becomes
![f(x) = \frac{1}{\sqrt 2} - \frac{1}{\sqrt 2}(x - \frac{3\pi}{4}) -\frac{1/\sqrt 2}{2!}(x - \frac{3\pi}{4})^2 +\frac{1/\sqrt 2}{3!}(x - \frac{3\pi}{4})^3 + ... +\frac{f^n(c)}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%20-%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%20-%5Cfrac%7B1%2F%5Csqrt%202%7D%7B2%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E2%20%2B%5Cfrac%7B1%2F%5Csqrt%202%7D%7B3%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E3%20%2B%20...%20%2B%5Cfrac%7Bf%5En%28c%29%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Rewrite as:
![f(x) = \frac{1}{\sqrt 2} + \frac{(-1)}{\sqrt 2}(x - \frac{3\pi}{4}) +\frac{(-1)/\sqrt 2}{2!}(x - \frac{3\pi}{4})^2 +\frac{(-1)^2/\sqrt 2}{3!}(x - \frac{3\pi}{4})^3 + ... +\frac{f^n(c)}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%20%2B%20%5Cfrac%7B%28-1%29%7D%7B%5Csqrt%202%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%20%2B%5Cfrac%7B%28-1%29%2F%5Csqrt%202%7D%7B2%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E2%20%2B%5Cfrac%7B%28-1%29%5E2%2F%5Csqrt%202%7D%7B3%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E3%20%2B%20...%20%2B%5Cfrac%7Bf%5En%28c%29%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Generally, the expression becomes
![f(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Hence:
![\sin(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=%5Csin%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
If the total bill is $85, and you want to leave a 15% tip, then you can calculate it as follows:
85 * 15%
= 85 * 15/100
= 85 * 0.15
= 12.75
The amount that should be left as a tip is D. $12.75.
Answer:
14
Step-by-step explanation:
multiples are the list of number that can be multiplied by a certain number.
list the multiples
make a chart
1 × 7 = 7 (odd)
2 × 7 = 14 (even)
the first even multiple is 14 (2×7)
Answer:
B.(–2, –7)
Step-by-step explanation: